Studying human resource management edited by Stephen Taylor; Carol Woodhams - Taylor, Stephen; Woodhams, Carol (London : Chartered Institute of Personnel and Development, 2017)
Excel at human resource management studies with this essential textbook.
Chapter - 01: Studying HRM [Stephen Taylor and Carol Woodhams];Chapter - 02: Managing and Co-Ordinating the HR Function [Krystal Wilkinson and Stephen Taylor];Chapter - 03: Business Issues and the Contexts of Human Resources [Stephen Taylor and Krystal Wilkinson];Chapter - 04: Developing Professional Practice [Ted Johns and Graham Perkins];Chapter - 05: Using Information in Human Resources [Graham Perkins and Carol Woodhams];Chapter - 06: Developing the Knowledge and Skill of the HR Professional [Carol Woodhams, Graham Perkins and Krystal Wilkinson]
Keywords: Personnel management -- Examinations -- Study guides; Personnel management -- Examinations